Impact of the COVID-19 Pandemic on Diabetic Ketoacidosis Patients Treated in a Pediatric Intensive Care Unit: A Single-Center Cross-Sectional Study - Eva Perak; Dina Mrcela; Josko Markic (Medicina)
Background and Objectives: Diabetic ketoacidosis (DKA) is a common complication of type 1 diabetes mellitus (T1DM) in children. Here, we explored the impact of the coronavirus disease 2019 (COVID-19) pandemic on the occurrence and severity of DKA in children in southern Croatia. Materials and Methods: The demographics and clinical and laboratory findings of all children and adolescents aged 0–18 years diagnosed with DKA and admitted to the pediatric intensive care unit (PICU) of the University Hospital of Split, Croatia from January 2013 to May 2023 were retrospectively collected. The participants were divided into two groups: (1) the pre-pandemic group (presenting before mid-March 2020) and (2) the pandemic group (presenting afterwards). Results: A total of 91 patients were included, 68 in the pre-pandemic and 23 in the pandemic group. The admission rate was similar (<1 patient per month) in both groups. In comparison to pre-pandemic patients, which mostly presented during the summer (52.9%) and winter seasons (23.5%), most pandemic cases occurred in spring (34.8%) and fall (30.4%, p = 0.002). No significant differences between the groups were identified in the severity of DKA, as reflected either by mean pH and median bicarbonate levels or by the proportion of patients with severe DKA. Nevertheless, HbA1c and triglycerides were significantly higher in the pandemic group (12.56% vs. 11.02%, p = 0.002 and 4.95 mmol/L vs. 2.8 mmol/L, p = 0.022, respectively) indicating poorer long-term glycemia. DKA complications were, overall, rare and without significant differences between the groups. Conclusions: The COVID-19 pandemic did not impact overall frequency or severity of DKA in children in southern Croatia. While the seasonal changes in DKA occurrence and a poorer long-term glycemia in pandemic patients may have been influenced by COVID-19 outbreaks and the imposed anti-pandemic measures, further studies are needed to determine if this was a temporary pandemic-related phenomenon or if this trend would persist in the future.